a ) 1.4-1.1.2+2.2.3-5=

b) 1.2:(-1.2.3)•2.1.4:(-3.3.5)•(-5.1.3)=


A 141122235 B 12123214335513 class=

Odpowiedź :

[tex]a)\\{}\quad \frac14-1\frac12+2\frac23-5=\frac3{12}-1\frac6{12}+2\frac8{12}-5= 2\frac{11}{12}-6\frac6{12}=2\frac{11}{12}-5\frac{18}{12}=-3\frac7{12}[/tex]

[tex]b)\\{}\quad\frac12:\left(-1\frac23\right)\cdot2\frac14:\left(-3\frac35\right)\cdot\left(-5\frac13\right)= \frac12:\left(-\frac53\right)\cdot\frac94:\left(-\frac{18}5\right)\cdot\left(-\frac{16}3\right)=\\\\=\frac12\cdot\left(-\frac35\right)\cdot\frac94\cdot\left(-\frac5{18}\right)\cdot\left(-\frac{16}3\right)= \frac12\cdot\left(-\frac31\right)\cdot\frac94\cdot\left(-\frac1{18}\right)\cdot\left(-\frac{16}3\right)=[/tex]

[tex]=\frac12\cdot\left(-\frac11\right)\cdot\frac94\cdot\left(-\frac1{18}\right)\cdot\left(-\frac{16}1\right)= -\frac12\cdot\frac94\cdot\left(-\frac1{9}\right)\cdot\left(-\frac{8}1\right)=\\\\= -\frac12\cdot\frac14\cdot\left(-\frac1{1}\right)\cdot\left(-\frac{8}1\right)= -\frac18\cdot\frac81=-1[/tex]